Mountain pine beetles and emerging issues in the management of woodland caribou in Westcentral British Columbia - Cichowski, Deborah; Williston, Patrick (Rangifer, 2005)
The Tweedsmuir—Entiako caribou (Rangifer tarandus caribou) herd summers in mountainous terrain in the North Tweedsmuir Park area and winters mainly in low elevation forests in the Entiako area of Westcentral British Columbia. During winter, caribou select mature lodgepole pine (Pinus contorta) forests on poor sites and forage primarily by cratering through snow to obtain terrestrial lichens. These forests are subject to frequent large-scale natural disturbance by fire and forest insects. Fire suppression has been effective in reducing large-scale fires in the Entiako area for the last 40—50 years, resulting in a landscape consisting primarily of older lodgepole pine forests, which are susceptible to mountain pine beetle (Dendroctonus ponderosae) attack. In 1994, mountain pine beetles were detected in northern Tweedsmuir Park and adjacent managed forests. To date, mountain pine beetles have attacked several hundred thousand hectares of caribou summer and winter range in the vicinity of Tweedsmuir Park, and Entiako Park and Protected Area. Because an attack of this scale is unprecedented on woodland caribou ranges, there is no information available on the effects of mountain pine beetles on caribou movements, habitat use or terrestrial forage lichen abundance. Implications of the mountain pine beetle epidemic to the Tweedsmuir—Entiako woodland caribou population include effects on terrestrial lichen abundance, effects on caribou movement (reduced snow interception, blowdown), and increased forest harvesting outside protected areas for mountain pine beetle salvage. In 2001 we initiated a study to investigate the effects of mountain pine beetles and forest harvesting on terrestrial caribou forage lichens. Preliminary results suggest that the abundance of Cladina spp. has decreased with a corresponding increase in kinnikinnick (Arctostaphylos uva-ursi) and other herbaceous plants. Additional studies are required to determine caribou movement and habitat use responses to the mountain pine beetle epidemic.